EVALUATION OF MIGRAINE AWARENESS AND ITS IMPACT ON STUDENTS OF NISHTAR MEDICAL UNIVERSITY - NOMAN , M; JAVID , MZ; JAMIL , MF; MANZOOR , A; SHAHID , M; LATIF , MK (Biological and Clinical Sciences Research Journal, 2024)
The cross-sectional study was conducted in Nishtar Medical Hospital from January 2022 to January 2023 to assess the prevalence, impact, and triggers of migraine in medical students. The study included both male and female students from all the years. The data was collected using a questionnaire containing questions regarding demographics, knowledge about migraine, character of pain, triggers, and accompanying factors. The questionnaire was standardised according to Migraine Disability Assessment Score (MIDAS) and International Headache Society (IHS) criteria. A total of 500 students were invited, of whom 470 (94%) completed the survey. The prevalence of migraine was 25.9% (122/470), and 50% (61/122) had more than five episodes in the last three months. Over one-third, 36% (44/122) of participants experienced severe pain. Moreover, 41% (50/122) sought medical advice, and 19.6% (24/122) were hospitalised. The most common symptoms experienced during an episode were unilateral headache (81.9%), pulsating headache (65.5%), photophobia (60%), and phonophobia (55.7%). The most common triggers were sleep deprivation (73.7%), stress (57.3%), loud sounds (55.7%), hunger (53.2%), and fatigue (51.6%). Of 122, 77 (63.1%) participants reported moderate to severe disability due to migraine attacks. It is concluded that migraine is prevalent among medical students and hurt the well-being and productivity of the students.